Proceedings of the 2025 2nd International Conference on Civil Engineering Structures and Concrete Materials (CESCM 2025) - Yanhui Liu; Sudharshan N. Raman; Fabio Tosti; Mohd Khairul Idham Mohd Satar (Atlantis Press International BV, 2025)
This is an open access book. The 2025 2nd International Conference on Civil Engineering Structures and Concrete Materials (CESCM 2025) is scheduled to take place on September 14–16, 2025 in London, UK. CESCM 2025 aims to convene pioneering academics and industrial experts in thefield of civil engineering structures and concrete materials for a shared discourse. The primary objective of the conference is to foster research and developmental activities in civil engineering structures and concrete materials, while also facilitating scientific information exchange among researchers, developers, engineers, students, and practitioners from across the globe. This annual conference serves as an ideal platform for individuals to exchange views and experiences pertaining to civil engineering structures and concrete materials as well as related areas.